1994
DOI: 10.1093/genetics/138.4.1293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci influencing wood specific gravity in an outbred pedigree of loblolly pine.

Abstract: We report the identification of quantitative trait loci (QTL) influencing wood specific gravity (WSG) in an outbred pedigree of loblolly pine (Pinus taeda L.). QTL mapping in an outcrossing species is complicated by the presence of multiple alleles (> 2) at QTL and marker loci. Multiple alleles at QTL allow the examination of interaction among alleles at QTL (deviation from additive gene action). Restriction fragment length polymorphism (RFLP) marker genotypes and wood specific gravity phenotypes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(5 citation statements)
references
References 16 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Following trigger technologies, including methods to detect polymorphisms in DNA, and QTL (quantitative trait locus) mapping in biparental crosses, MAS (marker assisted selection) was proposed as a way to dissect complex trait, carry out early selection and thus accelerate tree breeding [17,18]. A number of mapping studies soon followed, and seemingly major effect QTLs were mapped in several forest tree species [19][20][21], results that further hyped the curve, leading to a peak of inflated expectations. Well-grounded doubts had been casted, however, on the prospects of MAS in outbred trees [22], and results from simulation studies in crops indicated that QTLs (quantitative trait loci) were likely vastly overestimated in effect size and underestimated in numbers [23].…”
Section: Climbing the Slope Of Enlightenment Of Marker Assisted Fores...mentioning
confidence: 99%
“…Following trigger technologies, including methods to detect polymorphisms in DNA, and QTL (quantitative trait locus) mapping in biparental crosses, MAS (marker assisted selection) was proposed as a way to dissect complex trait, carry out early selection and thus accelerate tree breeding [17,18]. A number of mapping studies soon followed, and seemingly major effect QTLs were mapped in several forest tree species [19][20][21], results that further hyped the curve, leading to a peak of inflated expectations. Well-grounded doubts had been casted, however, on the prospects of MAS in outbred trees [22], and results from simulation studies in crops indicated that QTLs (quantitative trait loci) were likely vastly overestimated in effect size and underestimated in numbers [23].…”
Section: Climbing the Slope Of Enlightenment Of Marker Assisted Fores...mentioning
confidence: 99%
“…One of the priorities of plant genome mapping is the identification of genes associated with economically important traits and the use of this information for further improvement of crops. The value of molecular markers for the development of linkage maps and their use in the analysis of economically important traits has been amply demonstrated in both, field crops (Paterson et al 1991;Yu et al 1991;Mackill et al 1993;Paran and Michelmore 1993) and forest trees (Groover et al 1994;Bradshaw and Stettler 1995). Molecular linkage maps have been constructed for most major crop plants (Staub et al 1996;Paterson 1996); these maps provide a more direct method for the selection of desirable qualitative and quantitative traits through their linkage to easily detectable genetic markers (Edwards et al 1987;Paran and Michelmore 1993;Mackill et al 1993;Yao et al 1999).…”
Section: Marker Assisted Selectionmentioning
confidence: 99%
“…However, in outcrossing and highly heterozygous forest trees, up to four alleles can segregate at a single locus (Sewell and Neale 2000). This is because segregation results from separate meioses and crossovers in the two parents (Groover et al 1994). Where a QTL segregates for more than two alleles, there is an increased likelihood that allelic interactions such as simple dominance, over-dominance or under-dominance will occur (Groover et al 1994).…”
Section: Quantitative Trait Locus (Qtl) Mappingmentioning
confidence: 99%